(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
The article deals with the development of students’ environmental culture is increasingly recognized as a crucial component of holistic education, particularly in regions facing unique ecological challenges, such as the Republic of Karakalpakstan. This article explores pedagogical opportunities and practical mechanisms that can be modeled within high-class physical education (PE) classes to foster environmental awareness and sustainability values among students. This study identifies key strategies for embedding environmental topics into the PE curriculum, such as outdoor activities that encourage direct interaction with the natural environment, discussions on sustainable living, and the incorporation of ecologically themed games. Additionally, practical mechanisms like eco-sports initiatives, nature-based physical challenges, and community-driven projects offer students hands-on opportunities to engage with environmental issues. The pedagogical model proposed emphasizes active learning, critical thinking, and experiential education, making environmental culture a dynamic part of physical education